Comparação da detecção de autoanticorpos MOG-IgG pelo ensaio baseado em células avaliado pela imunofluorescência indireta por microscopia vs citometria de fluxo - Marchionatti, Amanda (2020)
Myelin oligodendrocyte glycoprotein (MOG) is a protein found exclusively in the central nervous system (CNS), expressed at the external layer of the myelin sheath and oligodendrocytes. MOG is an accessible target for autoantibodies, causing immune-mediated demyelination in CNS. MOG-IgG is detected by the cell-based assay (CBA), a technique that has improved the detection of clinically significant MOG-IgG binding. However, there are several factors that directly affect CBA, such as serum dilution and the reading method, which can be performed by indirect immunofluorescence analyzed under a microscope (CBA-IFI) or by flow cytometry (CBA-FC). The CBA-IFI is already widely used in clinical practice however the CBAFC still needs more studies to be standardized. There is still no consensus on which serum dilution to use or how best to analyze the results, which can be calculated by the ratio or delta of mean fluorescence intensity signal between MOG-expressing cells versus non-transfected cells. Thus, the objective of this work was to verify if there is a comparison between the detection of antibodies by indirect immunofluorescence versus flow cytometry, in addition to evaluating which is the best dilution and how to analyze the results obtained by the CBA-FC. For this, CBAIFI and CBA-FC were performed on serum of 104 patients with suspected positivity for MOG-IgG, with CBA-FC being performed at 1:20 and 1: 100 dilutions and their positivity value was evaluated by the ratio and the delta. The data obtained showed that the autoantibodies detected by the CBA-FC and CBA-IFI have 90.4% agreement and the CBA-IFI titles correlate with the CBA-FC positivity data, mainly analyzed by reason, at higher dilutions. Therefore, we concluded that both CBA-IFI and CBA-FC can be applied in the routine, as they are methodologies with complementary characteristics and benefits, revealing a more accurate result when MOG-IgG is detected by both.